Parenteral nutrition dysregulates bile salt homeostasis in a rat model of parenteral nutrition-associated liver disease - Koelfat, Kiran V K; Schaap, Frank G; Hodin, Caroline M J M; Visschers, Ruben G J; Svavarsson, Björn I; Lenicek, Martin; Shiri-Sverdlov, Ronit; Lenaerts, Kaatje; Olde Damink, Steven W M (Clinical nutrition (Edinburgh, Scotland), 2017)
BACKGROUND & AIMS: Parenteral nutrition (PN), a lifesaving therapy in patients with intestinal failure, has been associated with hepatobiliary complications including steatosis, cholestasis and fibrosis, collectively known as parenteral nutrition-associated liver disease (PNALD). To date, the pathogenesis of PNALD is poorly understood and therapeutic options are limited. Impaired bile salt homeostasis has been proposed to contribute PNALD. The objective of this study was to establish a PNALD model in rats and to evaluate the effects of continuous parenteral nutrition (PN) on bile salt homeostasis. METHODS: Rats received either PN via the jugular vein or received normal diet for 3, 7 or 14 days. Serum biochemistry, hepatic triglycerides, circulating bile salts and C4, IL-6 and TNF-alpha, and lipogenic and bile salt homeostatic gene expression in liver and ileum were assessed. RESULTS: PN increased hepatic triglycerides already after 3 days of administration, and resulted in conjugated bilirubin elevation after 7 or more days. This indicates PN-induced steatosis and impaired canalicular secretion of bilirubin, the latter which is in line with reduced hepatic expression of Mrp2 mRNA. There was no histological evidence for liver inflammation after PN administration, and circulating levels of pro-inflammatory cytokines IL-6 and TNF-α, were comparable in all groups. Hepatic expression of Fxr mRNA was decreased after 7 days of PN, without apparent effect on expression of Fxr targets Bsep and Shp. Nonetheless, Cyp7a1 expression was reduced after 7 days of PN, indicative for lowered bile salt synthesis. Circulating levels of C4 (marker of bile salt synthesis) were also decreased after 3, 7 and 14 days of PN. Levels of circulating bile salts were not affected by PN. CONCLUSIONS: This study showed that PN in rats caused early mild steatosis and cholestasis, while hepatic and systemic inflammation were not present. The onset of these abnormalities was associated with alterations in bile salt synthesis and transport. This animal model serves as an experimental model to further investigate the pathogenesis of PNALD inflicted by steatosis and cholestasis.
Keywords: Parenteral Nutrition; aspartátaminotransferasy; játra; gama-glutamyltransferasa; Hypoalbuminemia; Triglycerides; Bile Acids and Salts; Alkaline Phosphatase; Liver disease; alkalická fosfatasa; žlučové kyseliny a soli; Aspartate Aminotransferases; hyperbilirubinemie; Steatosis; Liver Diseases; cytokiny; parenterální výživa; Alanine Transaminase; Bilirubin; Intestinal Diseases; gamma-Glutamyltransferase; krysa rodu Rattus; FXR; zvířata; Bile salt signaling; nemoci střev; nemoci jater; triglyceridy; potkani Sprague-Dawley; Liver; homeostáza; Male; Hyperbilirubinemia; hypoalbuminemie; bilirubin; Homeostasis; Cytokines; Rats; alanintransaminasa; Rats, Sprague-Dawley; Animals; Parenteral nutrition; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech